Barriers to alcohol and other drug treatment use among Black African and Coloured South Africans - Myers-Franchi, Bronwyn (BIOMED CENTRAL LTD, 2013)
Background: There are racial disparities in the use of alcohol and other drug (AOD) treatment services in South Africa but little is known about the factors contributing to these disparities. This study aimed to redress this gap through identifying differences in barriers to AOD treatment use among Black African and Coloured persons from Cape Town, South Africa. The Behavioral Model of Health Services Utilization was used as an analytic framework.